Курганы VIII в. у села Астахово - Комар, А.В. (Степи Европы в эпоху средневековья, 2009)
The paper analyses excavation finds of barrow 4 of Astakhovo I and harrow 13 of Astakhovo III (the Don river basin) that was built in the Khazarian time and later was used by the Polovtsy as a sacral place. Original Khazarian barrow was constructed with black soil and stone cover and had a shape of a flat pyramid (with the square side 14 m at the bottom and 6 m at the top). SW-NF. orientated grave contained only remains of human and horse skeletons and grave goods due to grave robbing or some kind of a ritual in the Khazarian time. Preserved grave goods are as follows: a gold application a copy of a Byzantine solidus of Constantine IV (681 -685 A.D.): a silver application of a belt: a bronze pendant of a bell or a harness; an iron buckle; arrowhead and bone detail of the composite bow; iron plates, possibly, from armour, a fragment of the hand-made pottery. Barrow 13 of Astakhovo III presents burial with similar funeral rite but remains of burials goods here is much pooper: iron knife, bone plates from composite bow and saddle. Both Astakhovo harrows belongs to the NW group of the Sokolovskaia Balka type barrows and can be dated to the middle of the 8th century A.D.